2016
DOI: 10.1515/cer-2016-0029
|View full text |Cite
|
Sign up to set email alerts
|

Integration Processes In The Global Economy: Current State And Prospects. The Cases Of The European Union, ASEAN Economic Community, And NAFTA

Abstract: The aim of the paper is to determine the current state of the integration processes in the global economy and prognosticate on the foreseeable changes in this phenomenon in the upcoming. Will they be divergence from or continuity with the past trends in the global economy in this field? The article examines three regional integration groupings, i.e. the European Union, ASEAN Economic Community, and NAFTA. The analysis makes it possible to conclude that all of these groupings/organizations are encounter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Though the literature on economic convergence is vast (Bélanger and Mace, 2017;Zlatev et al, 2018), to the best of our knowledge this is the first study to look at awareness and expectation convergence within the context of international trade and technological diffusion. Our findings corroborate however with the past literature including Witkowska (2016), which looked at the state of the integration processes in the global economy, focusing on three regional integration groupings namely the European Union, the ASEAN Economic Community, and NAFTA. In the case of NAFTA, the study reported that member states do not seem to have an intention to deepen integration in the like of the European patterns and are not pushing NAFTA toward more advanced integration stages.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Though the literature on economic convergence is vast (Bélanger and Mace, 2017;Zlatev et al, 2018), to the best of our knowledge this is the first study to look at awareness and expectation convergence within the context of international trade and technological diffusion. Our findings corroborate however with the past literature including Witkowska (2016), which looked at the state of the integration processes in the global economy, focusing on three regional integration groupings namely the European Union, the ASEAN Economic Community, and NAFTA. In the case of NAFTA, the study reported that member states do not seem to have an intention to deepen integration in the like of the European patterns and are not pushing NAFTA toward more advanced integration stages.…”
Section: Discussionsupporting
confidence: 91%
“…Within the context of international trade, "Integration theory identifies the economic effectsboth short-term static and long-term dynamic -of particular stages of integration processes which should be expected within integrating economies such as free trade areas (FTA)" (Witkowska, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This growth implies increasing demand which, if not catered for, would lead to looming levels of food shortages [1]. Taking into account these and other dynamics, there is therefore a need not only for an increase in sustainable food supply and food security, but also efficient measures to redistribute that food to deprived economic regions [7,9]. It is within this broad context that African leaders have decided, perhaps for the first time, to look for internal ways to address Africa's perennial challenges of poverty and inequality at the continental level by signing the African Continental Free Trade Agreement (AfCFTA) in March, 2018 in Kigali Rwanda [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors include for the MRTA four emerging partnerships: the Regional Comprehensive Economic Partnership (REED), the Trans-Pacific Partnership (TPP), the Transatlantic Trade and Investment Partnership (TTIP), and the FTA between Japan, China and South Korea (JCKFTA). At the same time there are some authors consider a broader range of partnerships initiatives, but do not include JCKFTA [7,8]. However, the actual implementation of the MRTA is not going well.…”
Section: Resultsmentioning
confidence: 99%